Perilaku Konsumtif Mahasiswa Melalui Penggunaan Fitur Shopee Paylater dalam Perspektif Teori Jean Baudrillard - Christian, Vinsensius Dino Adi; Susanti, Antik Tri; Suwartiningsih, Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
Advances in communication technology, media, and informatics have influenced the world of trade which has led to e-commerce service with a new shopping atmosphere. The emergence of the Shopee application as one of the trading platforms provides the ShopeePayLater payment feature which is of interest to many people including students. This study aims to determine the effect of using ShopeePayLater by FISKOM UKSW students, and analyzed with consumptive behavior. This paper uses a qualitative approach with an in-depth interview method to several FISKOM UKSW students who are actively using the ShopeePayLater feature in the perspective of Jean Baudrillard's Theory of Consumer Society. The results of this study show that ShopeePayLater is not only influenced by functional needs, but also by symbolic motivations such as self-image and social status created through the ownership of certain items.